The Girls Creating Games Program. - Denner, Jill; Werner, Linda; Bean, Steve; Campe, Shannon (Frontiers: A Journal of Women Studies, 2005)
The article describes the Girls Creating Games (GCG), an after-school and summer program for sixth-through eighth-grade girls designed to address the barriers to girls' active participation in information technology. The program focuses on computer game development for two reasons. First, computer games are considered a gateway to more active use of technology. Not playing games disposes girls to relatively less active roles with the computer and delays improvement of spatial and problem-solving skills. The second reason for teaching game design and production is that it puts girls in the role of technology leaders, which can break down personal identity barriers as well as external barriers, such as gender role stereotyping and discrimination. Educators need to overcome several barriers to increase girls' active participation in technology. Personal barriers include lack of self-confidence, lack of fluency in technology skills, lack of early positive experiences, lack of information about careers, and a belief that technology careers require a solitary lifestyle in front of a computer.